Silicon microring resonator waveguide-based graphene photodetector - Amiri, Iraj Sadegh; Ariannejad, Mohammad Mahdi; Sorger, Volker J.; Yupapin, Preecha Promphan (Springer Verlag (Germany), 2019)
Here we study and analyze the performance of a graphene-based photodetector integrated onto a silicon-on-insulator microring using optical and electrical simulations. The electrical simulation reveals the role of material interface losses and allows one to extract key behavioral parameters such as dark current, responsivity and bandwidth.